PATHOPHYSIOLOGY OF ISCHAEMIC MITRAL VALVE PROLAPSE: A REVIEW OF THE EVIDENCE AND IMPLICATIONS FOR SURGICAL TREATMENT. Issue 1 (12th October 2017) - Nappi, Francesco; Spadaccio, Cristiano; Chello, Massimo
No abstract available